Implications of innovation for inclusive growth: a study of Medellín, Colombia's metro system and integral urban projects - Dols, Samantha (2015)
Medellín, Colombia continues to attract global recognition for its evolution from a crimesaturated and desegregated city to an award-winning paragon of innovation. Two innovations in particular, the Metro System & the Integral Urban Projects, have fostered and contributed to Medellín’s inclusive growth, as indicated by a corresponding increase in both social and economic capital. Through a mixed methodology analysis of these two experiences, including participant observation, in-depth interviews with different industry leaders, and household surveys, this thesis explores the extent to which inclusive innovation has contributed to inclusive growth in Medellín. The surveys were distributed to three sensitive neighborhoods of Medellín and apply a Synthesized Framework for measuring inclusive growth, one that includes five indicators for social capital and five indicators for economic capital, emphasizing the importance of progression in both dimensions. By drawing on concepts of inclusivity surfacing more frequently in business lexicon and the emergence of a newly branded Medellín, the findings of this thesis indicates that the implementation of innovations in association with a unified city vision practiced by the local government, corporate and non-profit sector has contributed to achieving inclusive growth, and has left civilians hungry for more.